Aggressive morphologic variants of mantle cell lymphoma characterized with high genomic instability showing frequent chromothripsis, CDKN2A/B loss, and TP53 mutations: A multi‐institutional study. Issue 8 (17th April 2020) - Streich, Lukas; Sukhanova, Madina; Lu, Xinyan; Chen, Yi‐Hua; Venkataraman, Girish; Mathews, Stephanie; Zhang, Shanxiang; Kelemen, Katalin; Segal, Jeremy; Gao, Juehua; Gordon, Leo; Chen, Qing; et al.
Abstract: Aggressive morphologic variants of mantle cell lymphoma (MCL), including blastoid and pleomorphic (B/P‐MCL), are rare and associated with poor clinical outcomes. The genomic landscape of these variants remains incompletely explored. In this multi‐institutional study, we describe recurrent mutations and novel genomic copy number alterations (CNAs) in B/P‐MCL, using next generation sequencing and SNP‐array. Chromothripsis, a recently described phenomenon of massive chromosomal rearrangements, was identified in eight of 13 (62%) B/P MCL cases, and a high degree of genomic complexity with frequent copy number gains and losses was also seen. In contrast, a comparative cohort of nine cases of conventional MCL (C‐MCL) showed no chromothripsis and less complexity. Twelve of 13 (92%) B/P‐MCL cases showed loss of CDKN2A / B (6 biallelic and 6 monoallelic losses); while only one C‐MCL showed monoallelic CDKN2A / B loss. In B/P‐MCL, TP53 was the most commonly mutated gene, with mutations present in eight cases (62%), six of which showed concurrent loss of chromosome 17p. Of the eight cases with chromothripsis, six (85%) harbored TP53 mutations. Other recurrent mutations in B/P‐MCL included ATM (7, 53%), CCND1 (5, 38%), NOTCH1 (2, 18%), NOTCH2, and BIRC3 (each in 3, 23%). Here, we describe high genomic instability associated with chromothripsis and a high frequency of CDKN2A/B and TP53 alterations in the aggressive variants of MCL. The nonrandom chromothripsis events observed in B/P‐MCL may be an indicator of clinically aggressive MCL. In addition, frequent CDKN2A deletion and high genomic instability may provide potential targets for alternative treatment.